Spatially Resolved Quantification of Ionomer Degradation in Fuel Cells by Confocal Raman Microscopy - Boehm, Thomas; Moroni, Riko; Breitwieser, Matthias; Thiele, Simon; Vierrath, Severin (Journal of The Electrochemical Society, 2019)
Ionomer membranes are crucial components ofmany electrochemical devices. In this work, confocal Ramanmicroscopy is employed to characterize Nafion ionomers quantitatively in pristine status and after usage as a proton exchange membrane in a fuel cell. Confocal Raman microscopy allows non-destructive thickness and equivalent weight measurements of Nafion with a 95% confidence interval of +/- 13 g mol(-1) at an equivalent weight of 1000 g mol(-1), which is significantly more accurate than previously reported methods. Characterization can be performed at a spatial resolution better than 2 mu m, providing insights into local membrane degradation after fuel cell operation. Membrane thinning to less than 40% of the initial thickness of Nafion NR-211 occurs after a 100 h open circuit voltage hold, accompanied by an anisotropic increase of the equivalent weight from 1035 g mol(-1) to an average of 1200 g mol(-1). Most pronounced increases are found close to the anode. Further, the characterization of a Nafion XL membrane shows that its microporous reinforcement is represented as increased equivalent weight with local heterogeneities within the membrane. These results show that confocal Raman microscopy is a valuable tool to investigate ionomers that are used as ion exchange membranes in electrochemical devices. (c) The Author(s) 2019. Published by ECS.
CRIS-Team WoS Importer:2019-03-15